Internet Based Control of Room Lights Using Wemos D1 - Rahmatulloh, Rizqi; Sunardi, Sunardi (Signal and Image Processing Letters, 2021)
The Internet of Things (IoT) has made things easier and cheaper because all devices are connected to the internet. Electronic equipment at home can be monitored and controlled remotely via internet so that it can be effective, easy, and automatic. This study builds lights as part of a smarthome that is used for lighting automatically using IoT. This study uses lamp automation method using equipment including the Wemos D1, LDR sensor, LCD, relay, and two lamps which are controlled using the Blynk application. This research has succeeded in building a remote home light monitoring system based on IoT in real time. The test has been carried out 24 times with 100% success. The house is no longer dark when the light intensity is low because the lights will automatically turn on, while if the light intensity is high, the lights will automatically turn off.